Rare Complication of IUCD Migration into the Urinary Bladder Presenting as Vesical Calculus: Case Report at Dr. Sikander Ali Mandhoro Civil Hospital, Badin - Akhtar, .; Aslam, Danish; Naeema, .; Nawaz, Sana (Biological and Clinical Sciences Research Journal, 2025)
Intrauterine contraceptive devices (IUCDs) are widely used, effective, and reversible, but rare complications include uterine perforation with extrauterine migration. Intravesical migration is uncommon and may serve as a nidus for vesical calculus formation, presenting with persistent lower urinary tract symptoms (LUTS) that are often misattributed. Objective: To describe the presentation, diagnostic pathway, and endoscopic management of an intravesically migrated IUCD with secondary bladder calcifications, emphasizing key follow-up and imaging considerations. Methods: This single-patient case report was conducted in the Department of Urology at Dr SAM CHB. The observation period spanned the index urology evaluation through a 1-week postoperative follow-up. The clinical data included a comprehensive history, a thorough examination, and relevant imaging studies. The diagnostic work-up consisted of a plain X-ray of the kidneys, ureters, and bladder (KUB), which revealed a metallic foreign body projected over the bladder, and ultrasonography, which demonstrated intravesical calcifications. The patient underwent diagnostic cystoscopy followed by same-session cystoscopic extraction of the IUCD with removal of adherent calcifications. Peri-operative outcomes and early symptom resolution were recorded. No statistical analysis was applicable due to the single-case design. Results: A 32-year-old woman with a 4-year history of dysuria, frequency, urgency, and intermittent fever had an IUCD inserted 5 years earlier that was presumed expelled after abnormal uterine bleeding; she subsequently conceived and delivered vaginally, with LUTS persisting postpartum. X-ray KUB identified a T-shaped metallic foreign body within the pelvis consistent with an IUCD; ultrasound confirmed intravesical calcifications. Initial management elsewhere was planned as an open cystolithotomy for presumed primary vesical calculus. On referral, cystoscopy revealed a partially encrusted IUCD within the bladder. Complete endoscopic removal of the IUCD and attached calcifications was achieved in a single session without complications. At 1-week follow-up, the patient reported complete resolution of LUTS. Conclusion: Intravesical IUCD migration, though rare, should be considered in women with unexplained LUTS and a history of IUCD insertion, especially when expulsion is suspected. Early use of plain radiography and targeted cystoscopy can expedite Diagnosis and enable minimally invasive, single-stage endoscopic removal, avoiding unnecessary open surgery. Routine post-insertion follow-up and prompt imaging when strings are not visualized or expulsion is suspected are essential to prevent delayed morbidity.